Combining Ability Study for Grain Yield and Agronomic Traits of Quality Protein Maize (Zea mays L.) Inbred Lines Adapted to Mid-Altitude Agroecology of Ethiopia - Lemi Mideksa Yadesa; Sentayehu Alamerew; Berhanu Tadesse (Agro Bali : Agricultural Journal, 2021)
In spite of the importance of quality protein maize to alleviate protein deficiency, almost all maize varieties cultivated in Ethiopia are normal maize varieties, which are devoid of lysine and tryptophan. Perusing the combining ability of QPM inbred for grain yield and its components is vital to design appropriate breeding strategies for the development of nutritionally enhanced maize cultivars. A line x tester analysis involving 36 crosses generated by crossing 9  elite maize inbred lines with 4 testers were evaluated for different desirable agronomic traits during the 2019 main season at BNMRC and JARC. The experiment was conducted using alpha lattice design with 3 replications. The objectives were to determine the combining ability of quality protein maize inbred lines, adapted to mid altitude agroecology of Ethiopia for agronomic traits. The crosses were evaluated in alpha lattice design replicated 3 times. Analyses of variances showed significant mean squares due to crosses for almost all the traits studied. GCA mean squares due to lines and testers were significant (P<0.05 or P<0.01) for most studied traits. SCA mean squares were also significant for most attributes across locations. The comparative importance of GCA and SCA variances observed in the current study for most studied traits indicated the preponderance of additive genetic variance in governing these attributes. Only L3 was the best general combiner for grain yield. Inbred line L3, for days to anthesis and L5 for days to silking had negative and significant GCA effects. L5 and L6 displayed negative and significant GCA effects for plant and ear height. Crosses, L2xT4, L3xT4, L4xT4, L5xT2, L6xT3, L7xT2, L9xT1 and L9xT4 were good specific combiners for grain yield. In general, these genotypes help as a source of promising alleles that could be used for forthcoming breeding work in the development of quality protein maize cultivars with desirable traits.